School based sexual and reproductive health education: students’ preferred learning style in secondary schools in Benue State, Nigeria (2018)
High risk sexual behaviours reported among adolescents in Benue state despite a decade of implementing Sexual and Reproductive Health Education ((SBSRHE) underscores the urgent need to examine the students preferred learning style on the premise that when teachers adapt instructional methods to suit the learners style it enhances knowledge and attitude change. Survey method was adopted to examine students preferred style of learning sexuality education measured with Barsch‘s Learning Style Inventory (α=0.72). One thousand eight hundred and twenty-four students consisting 925 (50.1%) males and 899 (49.3%) females were randomly drawn from nine secondary schools implementing Family life HIV Education (FLHE) in Benue state. Result reveal that of the 1824 students 916 representing 50.2 % of the sample prefers kinesthetic learning style; 768 (42.1 %) preferred learning by visual, while only 140 (7.7%) preferred learning by auditory. Of the 925 males 62.4% preferred learning using kinesthetic style while only 7.1% like to use auditory learning style. 486 females (54.1%) out of 899 preferred learning sexuality education with visual style while only 74(8.2%) preferred learning by auditory. Students learning style also differs by school location (rural, urban and semi-urban). The researchers concluded that irrespective of gender and school location majority of students in Benue state secondary schools preferred to learn sexuality education using kinesthetic style. This finding underscores the need for teachers of FLHE to diversify their delivery methods to suit all types of learners.